Efficacy of bevacizumab and chemotherapy in the first-line treatment of metastatic colorectal cancer: broadening KRAS-focused clinical view - Bencsikova, Beatrix; Bortlicek, Zbynek; Halamkova, Jana; Ostrizkova, Lenka; Kiss, Igor; Melichar, Bohuslav; Pavlik, Tomas; Dusek, Ladislav; Valik, Dalibor; Vyzula, Rostislav; Zdrazilova-Dubska, Lenka (BMC gastroenterology, 2015)
BACKGROUND: The aim of the present retrospective study was to analyze clinical outcome and risk factors associated with treatment outcomes according to KRAS status in patient with metastatic colorectal cancer (mCRC) treated with bevacizumab (bev) plus chemotherapy in the first-line setting. METHODS: We performed observational study on 1622 patients with mCRC treated with bev plus oxaliplatin- or irinotecan-based chemotherapy, and correlated treatment outcomes with KRAS mutation status. The primary endpoint was progression-free survival (PFS) and additionally overall survival (OS). Adverse events of bevacizumab and risk factors including location of metastases were evaluated. RESULTS: Mutation in KRAS was present in 40.6% of mCRC cases. The median PFS in patients with wild-type KRAS (wtKRAS) vs mutant KRAS was 11.5 vs 11.4 months, respectively. The median OS was 30.7 vs 28.4 months (p = 0.312). Patients with KRAS mutation had lung metastases more frequently than wtKRAS individuals (32.0% vs 23.8%; p = 0.001). We observed no difference in clinical outcome between hepatic and extrahepatic metastatic disease. CONCLUSION: KRAS mutation does not interfere with clinical benefit from first-line treatment with bevacizumab plus chemotherapy in mCRC patients.
Keywords: mutace; Capecitabine; Proto-Oncogene Proteins p21(ras); dospělí; Oxaloacetates; kolorektální nádory; Female; ras Proteins; kamptothecin; Fluorouracil; Adult; ženské pohlaví; mladý dospělý; Oxaliplatin; Deoxycytidine; přežití bez známek nemoci; nádory plic; Colorectal Neoplasms; lidé; bevacizumab; nádory jater; capecitabinum; Mutation; Aged, 80 and over; protoonkogenní proteiny; míra přežití; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; organoplatinové sloučeniny; oxaliplatin; deoxycytidin; retrospektivní studie; Liver Neoplasms; Male; Bevacizumab; fluoruracil; Aged; Young Adult; Proto-Oncogene Proteins; irinotekan; Leucovorin; Disease-Free Survival; Lung Neoplasms; Survival Rate; lidé středního věku; senioři nad 80 let; Organoplatinum Compounds; senioři; mužské pohlaví; Camptothecin; oxalacetáty; Irinotecan; leukovorin; Retrospective Studies; protoonkogenní proteiny p21(ras); Middle Aged; Ras proteiny; Humans